2015
DOI: 10.4088/jcp.14m09162
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants Are Not Overprescribed for Mild Depression

Abstract: Objective Evaluate over-prescribing of antidepressant medication for minimal or mild depression. Method Electronic records data from four large healthcare systems identified outpatients aged 18 or older starting a new episode of antidepressant treatment with an ICD9 diagnosis of depressive disorder (296.2, 296.3, 311, or 300.4). PHQ9 depression severity scores at time of treatment initiation were used to examine the distribution of baseline severity and the association between baseline severity and patients'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
1
19
1
Order By: Relevance
“…The proportion of prescribing without a depression diagnosis was less than the 72.7% described by Mojtabai and Olfson in their NAMCS analysis (8), yet higher than the 26% found by Simon et al (13), which is likely a function of the respective data sources. NAMCS limits the number of visit diagnoses reported to just 3, so there may be visits for MDD occurring that do not get captured in NAMCS because MDD is in a lower position on the problem list.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The proportion of prescribing without a depression diagnosis was less than the 72.7% described by Mojtabai and Olfson in their NAMCS analysis (8), yet higher than the 26% found by Simon et al (13), which is likely a function of the respective data sources. NAMCS limits the number of visit diagnoses reported to just 3, so there may be visits for MDD occurring that do not get captured in NAMCS because MDD is in a lower position on the problem list.…”
Section: Discussioncontrasting
confidence: 60%
“…Finally, a recent analysis of participants in the Baltimore Epidemiologic Catchment Area Study followed for 4 survey waves from 1981–2005 found that, among antidepressant users in the final wave, 69% did not currently and had never met criteria for MDD based on their survey assessments over the preceding 2 decades. Even a recent analysis arguing that antidepressant use without MDD is not a significant problem found that, among those ≥65 and newly-prescribed an antidepressant, 26% had symptoms below the threshold that suggests MDD (13). …”
Section: Introductionmentioning
confidence: 99%
“…Depression diagnoses were identified using ICD9‐CM visit diagnoses: 296.2X, 296.3X, 311, 309.0, 309.1 and 300.4. Recorded diagnoses of depression indicate clinically significant depressive symptoms as confirmed by PHQ9 . Suicidal ideation was identified using either PHQ9 questionnaires from the Epic/Clarity electronic health record (EHR) databases, where item 9 (thoughts of death or self‐harm) contained a score of 2 (‘more than half the days’) or 3 (‘nearly every day’); or ICD‐9‐CM diagnosis V62.84 (if not accompanied by an ICD9‐CM code indicating injury or poisoning).…”
Section: Methodsmentioning
confidence: 99%
“…Using methods previously described (5), health system records identified adult outpatients beginning a new episode of antidepressant treatment for a depressive disorder between 1/1/2010 and 12/31/2012. Self-reported race/ethnicity was identified from electronic medical records.…”
Section: Methodsmentioning
confidence: 99%